VALUE STREAM MAPPING FOR WASTE IDENTIFICATION IN THE LOW COST HOUSE CONSTRUCTION PROCESS (CASE STUDY: XYZ HOUSING - Nurlaelah Nurlaelah (University Of Muhammadiyah Jakarta, 2022)
XYZ housing is a low cost housing created by developers with low-income individuals in mind. However, a lot of individuals bemoan the state of their houses because of flaws like leaks, peeling paint, and other issues. This is unquestionably connected to the way the contractor handled the construction process. When there are signs of waste, particularly when there are delays and waste inventories, it is possible that there will also be additional sorts of waste throughout implementation. By employing the value stream mapping method, this study seeks to both detect and simultaneously minimize or eliminate waste that happens during the construction of affordable homes. Two key tasks are completed: creating an overview of the current state map, which represents the state of the development process currently, and offering solutions and suggestions for improvement given as a future state map.